2012
DOI: 10.1016/j.newast.2012.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Physical parameters of some close binaries: ET Boo, V1123 Tau, V1191 Cyg, V1073 Cyg and V357 Peg

Abstract: With the aim of providing new and up-to-date absolute parameters of some close binary systems, new BVR CCD photometry was carried out at the Ankara University Observatory (AUG) for five eclipsing binaries, ET Boo, V1123 Tau, V1191 Cyg, V1073 Cyg and V357 Peg between April, 2007 and October, 2008. In this paper, we present the orbital solutions for these systems obtained by simultaneous light and radial velocity curve analyses. Extensive orbital solution and absolute parameters for ET Boo system were given for … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Their results are in good agreement with those presented by Deb & Singh (2011). Ekmekçi et al (2012) obtained new BVR photometric observations and derived a somewhat larger orbital inclination of i = 74 • , which resulted in slightly smaller masses than those given by Deb & Singh (2011) and Zhang et al (2011).…”
Section: V1123 Taumentioning
confidence: 78%
See 1 more Smart Citation
“…Their results are in good agreement with those presented by Deb & Singh (2011). Ekmekçi et al (2012) obtained new BVR photometric observations and derived a somewhat larger orbital inclination of i = 74 • , which resulted in slightly smaller masses than those given by Deb & Singh (2011) and Zhang et al (2011).…”
Section: V1123 Taumentioning
confidence: 78%
“…They found it to have an orbital inclination of i = 73.2 • , a contact configuration with fill-out factor of f = 10 per cent and a temperature difference between the components ∆T = 562 K. The resulting physical parameters were: M1 = 1.720 ± 0.015M ⊙ and M2 = 0.690 ± 0.013M ⊙ . Ekmekçi et al (2012) used their BV R band photometric data and the spectroscopic mass ratio from Rucinski et al (2008) and arrived at a model with a similar inclination but a higher fill-out factor (31.2 per cent). The temperatures of the components differ by 300 K. A somewhat different absolute parameters than those in Deb & Singh (2011) were determined: M1 = 0.85 ± 0.03M ⊙ and M2 = 0.34 ± 0.02M ⊙ .…”
Section: V357 Pegmentioning
confidence: 99%
“…We also note that in the cases of three objects (SW Lac, V357 Peg, V781 Tau), physical parameters (especially the effective temperatures) adopted from the most recent analyses (Şenavcı et al 2011;Ekmekçi et al 2012;Li et al 2016, respectively) did not result in well-fitted models of our observed spectra. In these cases, we decided to adopt physical parameters from earlier studies (Gazeas et al 2005;Deb & Singh 2011;Kallrath et al 2006, respectively), which allowed us to construct better models.…”
Section: List Of Targetsmentioning
confidence: 62%
“…Strohmeier (1960) first recognized the variability of V1073 Cyg, then the photographic (pg) light curve was published in 1962 (Strohmeier 1962). Thus far, more photometric and spectrographic researches have been carried out for V1073 Cyg (such as Sezer 1993;Morris & Naftilan 2000;Yang & Liu 2000;Ekmekc ¸i et al 2012), and absolute parameters have been derived. Here is a brief introduction.…”
Section: Introductionmentioning
confidence: 99%